Performance evaluation of MPEG-4 visual error resilient tools over a mobile channel - Chang, , YC; Tang, , TF; Beg, , MS (2003)
MPEG-4 is the most recent standard for audiovisual representation published by International Organization for Standardization, targeted for future interactive multimedia video communications calling for content-based functionalities, universal access in error prone environments and high coding efficiency. Besides the provisions for content-based functionalities, MPEG-4 video coding standard will assist the efficient storage and transmission of very low bit rate video in error prone environments. This makes MPEG-4 a good candidate for video coding standard for Terrestrial Trunked Radio Standard (TETRA) video transmission. This paper presents the overall performance of a communication system used to transmit MPEG-4 encoded video over TETRA channels. The video quality that can be achieved at different channel conditions employing different combination of MPEG-4 built-in error resilient tools are presented in this paper.